Ethnobotanical survey of medicinal plants used by the Agta community in Gonzaga, Cagayan, Philippines - VENUS B. GUIMBUAYAN; CECILIA S. CORDERO; GRECEBIO JONATHAN D. ALEJANDRO (Society for Indonesian Biodiversity, 2025)
Abstract. Guimbuayan VB, Cordero CS, Alejandro GJD. 2025. Ethnobotanical survey of medicinal plants used by the Agta community in Gonzaga, Cagayan, Philippines. Biodiversitas 26: 6316-6334. Traditional knowledge of medicinal plants remains an integral part of primary healthcare systems in the Philippines, especially among indigenous communities. This study aimed to document the medicinal plant species used by the Agta indigenous peoples of Gonzaga, Cagayan, Philippines. From August 2024 to February 2025, 34 key informants were selected through purposive sampling and interviewed using a semi-structured questionnaire. Data were analyzed to determine the most culturally important species using Use Value (UV) and Informant Consensus Factor (ICF). Disease categories were classified in accordance with the World Health Organization International Classification of Diseases, 11th Revision (WHO-ICD 11). The Agta community reported 81 medicinal plant species, representing 74 genera and 37 families, with Poaceae being the most represented family (nine species). Leaves were the most commonly used plant part (41%), and decoction (43%) was the most frequent mode of preparation. Myristica sp. and Vitex arvensis were the most cited species, with UVs of 0.88 and 0.62, respectively. The highest ICF value (1.0) was recorded for disease category 5 (endocrine, nutritional, or metabolic diseases), followed by the Disease Categories 12 (Diseases of the Respiratory System) and 18 (Pregnancy, childbirth or the puerperium) and with ICF values of 0.76 and 0.71, respectively. This study provides the first documentation of the medicinal flora used by the Gonzaga Agta, offering a comprehensive inventory that underscores its dual significance for safeguarding cultural heritage and guiding future pharmacological research.